Strategi Kewirausahaan dan Tantangan Pengelolaan Usaha Kuliner Kawasan Pesisir Pada Café Berkah Fitria Raffa di Kelurahan Talise - Dina Hardianti; Nanda Aprilia Royna; Phiter Boni Parubak; Suci Handayani; Meinar Meinar; Nuraisyah Nuraisyah; Fachrul Reza; Andi Maman Firmansyah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Cafe Berkah Fitria Raffa in Talise Village is a culinary business that continues to grow by implementing various entrepreneurial strategies. Located on the beach, with a cool and comfortable atmosphere, making it a favorite place for visitors while enjoying the sea view. This study aims to analyze the entrepreneurial strategies implemented and the obstacles experienced by Cafe Berkah Fitria Raffa in Talise Village in running its business. The method used is a case study with a Qualitative approach with data collection through interviews, observations, and documentation. Research findings show that the success of the Cafe is supported by several strategies including maintaining the cleanliness of the place, providing friendly service, decorating the place, and providing a variety of menus including heavy meals, snacks, and drinks at affordable prices so that Cafe Berkah Fitria Raffa is always busy compared to other cafes around it. based on the results of the study, this business experiences several main obstacles, namely if there is rain and strong winds which cause the Cafe to be empty of visitors.